Stress sndrome:cause, symtoms and coping strategies (2006)
Stresses, which can be described as an organism's total response to experimental demands or pressure is conceptualized in this paper as a normal part of life that can help an individual learn and grow. The paper after reviewing some theories of stress from the perspective of the models of stress as stimulus, as response and a process;points that stress has only one causenamely: stressors. Stressors are those major events in an individual's daily life that drains the emotions. These stressors differs by way of type, time of happening, situatinal context and intensity. Though stress can manifest itself phyiscally, emotionally and or mentally depending on the stressors and the types of changes or events being dealt with, the paperx-rayed the three major stages through which stress manifests. The paper concludes by discussing possible coping strategies, which can be employed in dealing wiht stress.